2022
DOI: 10.21462/jeltl.v7i2.818
|View full text |Cite
|
Sign up to set email alerts
|

Men’s Language and Masculine Identity Construction in Sexist Jokes

Abstract: <em>The power imbalance between men and women in society is reflected in their language use and it may be reinforced in sexist jokes. This is a sociolinguistic study on men’s language in sexist jokes on the Internet. This study is aimed at investigating men’s linguistic features and the masculine identities represented by those features. This is a descriptive qualitative study with complementary quantitative analysis. The theories of Tannen’s men language (1990) and Kiesling’s masculine identities (2007)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Nursanti investigated how men's language in sexist jokes reflects and constructs masculine identities, focusing on the Internet as the context (Nursanti, 2022). The study identified dominant masculine identities in such jokes, highlighting men's use of language to assert social dominance and solidarity.…”
Section: Introductionmentioning
confidence: 99%
“…Nursanti investigated how men's language in sexist jokes reflects and constructs masculine identities, focusing on the Internet as the context (Nursanti, 2022). The study identified dominant masculine identities in such jokes, highlighting men's use of language to assert social dominance and solidarity.…”
Section: Introductionmentioning
confidence: 99%